Evaluation of Effective Strategies for Passing Acceptance at State and Official Universities in 2022 - Sudarti Sudarti; Elok Permatasari; Albertus Djoko Lesmono (Pascasarjana Universitas Mataram, 2023)
Along with the increasingly modern developments, higher education has a significant contribution to improving the quality of human resources. However, the lack of student motivation to continue on to tertiary education is one of the indicators that we need to address. This activity aims to motivate MA/SMA/SMK students to continue their studies at tertiary institutions and official services, as well as to increase knowledge, understanding, and master strategies for passing into PTN and official services in 2022. This activity is carried out ONLINE through virtual zoom meetings and whatsapp group, targeting MA/SMA/SMK students. The stages of carrying out this activity, 1) Preparation by the service team and the ILBG Galileo Jember team, 2) online webinars every Sunday, especially on January 16, January 23, and February 6 2022, 3) Online assistance through washtapp ghroup, 4) Evaluation, 5) Reporting. The expected results of this activity include, 1) Increased motivation of MA/SMA/SMK students to enter tertiary institutions and official services, 2) Increased student understanding of strategies for passing to PTN and official services, 3) Increased student mastery in understanding material and test questions selection to enter tertiary institutions and official services, 4) students better understand how to choose the right major strategy.